(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
The importance of the current research lies in identifying the impact of the (IPAGA) model on the cognitive achievement of students of the second stage / College of Physical Education and Sports Sciences, which is based on the basis that the new knowledge of the learner is formed with the help of his old knowledge by building connections between them, resulting in new ideas, and that the representation of these ideas actually, it does not take place unless the learner actively participates in it, this deviates from the traditional lessons. It also creates an educational environment that takes into account individual differences in the learning process and makes the student positively productive by linking the theoretical side with the practical, which is a modern and organized attempt according to advance preparation in the educational field. The aim of the current research is to prepare a measure of cognitive achievement for students of the second stage of the College of Physical Education and Sports Sciences, as well as to identify the impact of the I.P.A.G.A model on students’ cognitive achievement, and to identify the learning advantage between the control and experimental groups. The researcher used the experimental method and designed equal control and experimental groups with pre and post-tests, and the research community included the students of the second stage in the College of Physical Education and Sports Sciences - University of Babylon for the academic year (2021-2020), who numbered (201), and two divisions were selected, namely (A,C). Division (C) represented the experimental group and division (A) represented the control group. (30) students were selected as a research sample, (15) in the experimental group and the same as in the control group, and (10) students in an exploratory sample also by simple random method. The results showed through the table that there are significant differences between the results of the pre-test and the post-test in favor of the post-test of the experimental group in the variables under consideration (cognitive achievement).